Is Procrastination Related to Low‐Quality Data? - Voss, Nathaniel M.; Vangsness, Lisa (Educational measurement, issues and practice, 2020)
While it is easy to assume that university students who wait until the last minute to complete surveys for their class research requirements provide low‐quality data, this issue has not been empirically examined. The goal of the present study was to examine the relation between student research procrastination and two important data quality issues—careless responding and measurement noninvariance. Data gathered from university students across two semesters tentatively indicated that procrastination is related to low‐quality survey data. Procrastination was slightly more problematic for certain data quality issues (measurement noninvariance) than others (careless responding). These relations, however, were small and contingent on how procrastination and careless responding were measured. Accordingly, it seems more beneficial for researchers to select a sampling window that supports their research goals and statistical power requirements rather than select a sampling window that attempts to minimize careless survey responding or other measurement issues.